PENINGKATAN PERKEMBANGAN MOTORIK HALUS ANAK MELALUI PERMAINAN MERONCE DENGAN TUTUP BOTOL DI KELOMPOK A TK NEGERI PEMBINA MUARA BULIAN - Nurhayani Ritonga; Patmawati Patmawati (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Kindergarten-age children have characteristics like to play, therefore the development of children's abilities in various aspects must be done by playing, in line with that this study aims to see an increase in children's fine motor development by using bottle cap type meronce games. This research was designed using Class Action Research with four stages of each cycle, namely planning, action, observation and reflection, data collection techniques carried out with observation sheets and tests. From the implementation of the action is known that the use of bottle cap type meronce can improve the development of fine motor children, this statement is based on before the action of kindergarten children are still many who have not been able to use their fingers in fine motor activities, but after the action until cycle 3 seen kindergarten children have increased motor development. The successful use of the game is inseparable from the collaboration between researchers and teachers, so that what is needed and in accordance with the condition of kindergarten children group A can be designed, implemented properly. The implication of this research in the field of education is that the limitations of media in educational institutions can be innovated by utilizing objects available in the school environment, so that objects that were initially seen as garbage with teacher innovation are useful as a learning medium.